Exploration of Relational Thinking Skills Using Problem Solving of Geometry Transformation - Ramadhan, Sahrul; Effendi, Moh Mahfud; Ummah, Siti Khoiruli (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
The aimed study is analyzing the mathematical ability of students with relational thinking skills in geometry transformation material. This study used a descriptive qualitative approach. Data collection techniques were carried out by giving tests based on contextual problems and interviews. The test result was used to measure the effectiveness and completeness of learning outcomes. Furthermore, the result of the interviews supported the data of test results and identified the problem that was faced during the process of the test. The research showed that the most achieved indicator is the first indicator which can write the important information and create the relation about the description of the problem. Meanwhile, the least indicator that has been achieved was the third and fourth indicator which analyzed the relation by using structures, symbols, and properties to find models and re-check in the form of sketching and operating matrices transformation.Tujuan dari penelitian ini yaitu “mengkaji kemampuan matematis peserta didik dengan relational thinking skill pada materi transformasi geometri”. Penelitian ini menggunakan deskripstif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan memberikan soal tes berbasis permasalahan kontekstual dan wawancara. Hasil test digunakan untuk mengukur keefektifan dan ketuntasan hasil belajar. Selanjutnya hasil wawancara mendukung data dari hasil tes dan mengidentifikasi masalah yang dihadapi selama proses tes. Hasil penelitian menunjukkan bahwa Indikator yang paling banyak dicapai yaitu indikator pertama yang mana mampu menuliskan informasi penting dan membentuk relasi tentang gambaran sebuah masalah. Sementara itu, indikator yang paling sedikit dicapai adalah indikator ketiga dan keempat yang mana menganalisis relasi dengan menggunakan struktur, simbol, dan sifat untuk mencari model dan mengecek kembali dalam bentuk sketsa dan operasi transformasi matriks.